ESTONIAN YOUTH WORK EXPERTS PROFESSIONAL GROWTH: CASES STUDY - Veigel, Maarika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Estonian youth work (YW) has been in development almost 30 years. In the last more than 15 years the same trends have been observed in the studies in terms of professional development: the shortage of employees with professional education and workers high mobility. At the same time, the progressive decisions and regulations made in Estonia, on the field of European YW are exemplary. Thus, the prerequisites for professional YW were created and experts in the field have also developed.The aim of research was to give an overview of the stories of becoming as experts. Semi-structured interviews were compiled in 2019. Special focus was on the professional growth in the content of life story. The study revealed both – randomness entry into YW, but various supporting external aspects (active school life, supportive community, camps). However, the most important were the personal factors - motivation, consistency, entrepreneurship, courage, YW studies, participation in (foreign) projects, mission. Professional knowledge and skills supported mostly the development from a novice specialist into an advanced employee and expert. Commitment, autonomy were the main work-load impact factors. The desire to work with young people has brought some retired youth workers back to YW. Horizontal career was limited but usual.